Neurometabolic Therapy for Parkinson's Disease - N. G. Zhukova; A. Ya. Masenko; K. S. Kuznetsova; N. A. Kicherov; I. A. Zhukova; O. V. Gaponova (Лечащий Врач, 2023)
Parkinson's disease is characterized by a combination of motor and non-motor symptoms. One of the most common non-motor symptoms is asthenia, the prevalence of which in the structure of Parkinson's disease is 37.7-81.6%, depending on the stage. Due to the insufficient effectiveness of standard antiparkinsonian therapy for asthenia, it is advisable to study additional methods for correcting this condition. Our aim was to evaluate the clinical efficacy of the drug fonturacetam in patients with Parkinson's disease as an additional therapy for the correction of asthenic syndrome. A clinical comparative observation of 50 patients with Parkinson's disease of various stages and symptoms of asthenia was carried out. Patients were randomly assigned to 2 groups: the main group (n = 30), where in addition to basic antiparkinsonian therapy, fonturacetam was prescribed at a dose of 200 mg per day, divided into 2 doses; the control group (n = 20), where patients received only basic therapy. The course of therapy with fonturacetam was 30 days, the total duration of follow– up was 60 days. The effectiveness of treatment was assessed on the scales of asthenia MFI-20 (before (Visit 1), after treatment (Visit 2), 1 month after completion of treatment (Visit 3)); anxiety and depression HADS (Visits 1, 2); daytime sleepiness and the risk of sudden falling asleep Epworth (Visits 1, 2). In the main group, there was a distinct statistically significant effect of therapy after completion of the course (p = 0.00091), as well as in the follow–up period according to the MFI-20 scale (median values of the total score of 58 points, 48.5 and 50.5 at visits 1, 2, 3, respectively), while the most significant changes were observed in patients with Stage II according to Hoehn and Yahr, while an increase in asthenic symptoms was recorded in the control group. According to the HADS scale, there was a decrease in the severity of depression symptoms in the main group (the dynamics of scores was from 7 to 5, p = 0.01853); no such effect was observed in the control group. When assessing daytime sleepiness, patients of the main group noted a subjective improvement by visit 2, however, according to the Epworth scale, there were no statistical changes in both the main and control groups. The drug fonturacetam has significant antiasthenic and antidepressant effects in patients with Parkinson's disease, while the effect of therapy on the symptoms of asthenia is prolonged. Fonturacetam in a daily dose of 200 mg may be recommended for use in patients with Parkinson's disease as an adjunct to the main antiparkinsonian therapy.